A Multidisciplinary Analysis encompassing Nursing, Pharmacy, Gynecology, General Practice, Physical Therapy, Laboratory, Health Information, and Public Health to streamline Health Care Organizations - Ali Hussain Al-Essa,; Faisal Rimthan Al Anazi,; Nouf Mohammed Alali,; Zainab Yousef Al Rebh,; Saad Mohammed Awadh Algarni,; Hamad Suliman Hamad Alkhuriji,; Fuad Ibrahim Al Nami,; Faez Saud Almutairi,; Sana Naha Baker Alkhaibari,; Salwa Shadad Almutairi,; Hadeel Sultan Ibrahim Alasiri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The complexity of modern health care organizations necessitates the integration of various health care specialties to achieve optimal patient outcomes, enhance service efficiency, and ensure sustainability. This review investigates the multidisciplinary approach involving nursing, pharmacy, gynecology, general practice, physical therapy, laboratory services, health information management, and public health. Each of these sectors contributes uniquely to the overall care continuum, and their integration is key to streamlining health care delivery. This paper explores the roles, collaborative potential, and synergies of each specialty in improving care coordination, addressing the social determinants of health, and optimizing resource utilization. Emphasis is placed on the importance of interprofessional collaboration and information sharing in facilitating holistic, patient-centered care. The article also delves into the potential challenges associated with multidisciplinary collaboration, such as communication barriers, varying professional priorities, and organizational constraints. Finally, the review outlines strategies for overcoming these obstacles, including interprofessional education, technological integration, and policy reform. The overall goal is to showcase how a multidisciplinary approach not only improves patient care but also contributes to the long-term efficiency and effectiveness of health care organizations.